Changing perspectives on guardianship against crime: an examination of the importance of micro-level factors. Issue 4 (November 2018) - Reynald, Danielle; Moir, Emily; Cook, Alana; Vakhitova, Zarina
Abstract This paper focuses on how the narrative around guardianship as a crime prevention strategy has evolved from its original roots in macro-level theory and examination predominantly in residential places with a focus on property crime. It first highlights the ways in which some of the most useful insights about how guardianship functions to protect against crime have been illuminated by micro-level studies which have built on macro-level trends. Recent scholarship is used to illustrate how criminological understanding about guardianship against crime has been significantly developed through a focus on micro-level environmental factors and, most recently, individual factors. Perhaps one of the most significant developments in guardianship research in recent years has been its application beyond the residential context to extend to interpersonal crimes (sexual crimes in particular) and to cybercrime (cyberabuse in particular). Conclusions are drawn about how these new developments can be interwoven to advance the theoretical underpinnings of guardianship.